2004
DOI: 10.1124/jpet.104.067983
|View full text |Cite
|
Sign up to set email alerts
|

Altered Pharmacology of Synaptic and Extrasynaptic GABAAReceptors on CA1 Hippocampal Neurons Is Consistent with Subunit Changes in a Model of Alcohol Withdrawal and Dependence

Abstract: Previously, we reported (Cagetti, Liang, Spigelman, and Olsen, 2003) that chronic intermittent ethanol (CIE) treatment leads to signs of alcohol dependence, including anxiety and hyperactivity, accompanied by reduced synaptic ␥-aminobutyric acid (A) receptor (GABA A R) function and altered sensitivity to its allosteric modulators consistent with a measured switch in subunit composition. In this study, we separated the synaptic and extrasynaptic components of GABA A R activation in recordings from pyramidal CA1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
138
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(158 citation statements)
references
References 62 publications
17
138
3
Order By: Relevance
“…3A,B). These are values approximately two-fold greater than observed under control conditions (P<0.001), similar to previous reports (Liang et al, 2004). A lower concentration of THIP (5 μM) produced a 70-80 pA current following steroid treatment, while the THIP-generated current recorded under control conditions was barely detectable.…”
Section: Thip and La 3+ Effects On Hippocampal Current In The Slicesupporting
confidence: 73%
See 1 more Smart Citation
“…3A,B). These are values approximately two-fold greater than observed under control conditions (P<0.001), similar to previous reports (Liang et al, 2004). A lower concentration of THIP (5 μM) produced a 70-80 pA current following steroid treatment, while the THIP-generated current recorded under control conditions was barely detectable.…”
Section: Thip and La 3+ Effects On Hippocampal Current In The Slicesupporting
confidence: 73%
“…This tonic current is also a major target of GABA-modulatory drugs such as BDZs, anesthetics, barbiturates, steroids and ethanol (Bai et al, 2000;Belelli and Herd, 2003;Liang et al, 2004;Stell et al, 2003;Wei et al, 2004). Our data as well suggest that the tonic component produces a greater response to BDZs recorded under control conditions.…”
Section: Discussionsupporting
confidence: 58%
“…Thus, the hippocampus may be one of several brain regions in the limbic neuroanatomical circuit underlying PTZ-induced convulsions whereby line differences in GABA A receptors exist. Certainly, chronic ethanol exposure and withdrawal significantly alters the expression and peptide levels of several GABA A receptor subunits in the hippocampus of male rats (↓ α1, ↑ α4, ↑ γ2, ↓ δ; Cagetti et al, 2003;Grobin et al, 2000;Matthews et al, 1998), but the relevance of these changes in expression to GABA A receptor subunit assembly or trafficking, composition of synaptic versus extra-synaptic receptors, or phosphorylation state of GABA A receptors (see Kumar et al, 2004;Liang et al, 2004) to the present findings is not known. Additional factors influencing GABA A receptor function are the rapid diffusion of hippocampal receptors from extra-synaptic to synaptic domains (Thomas et al, 2005) and GABA A receptor associated proteins (Chen and Olsen, 2007).…”
Section: Discussionmentioning
confidence: 68%
“…Other studies have reported increases in either the ␥2 or ␣4 subunit (Brooks-Kayal et al, 1998;Fritschy et al, 1999). Similar, potentially interrelated changes in the ␦, ␣4, and ␥2 subunits have also been observed in a chronic, intermittent, ethanol model of alcohol withdrawal (Cagetti et al, 2003) that exhibits decreased inhibition and a decreased threshold for pentylenetetrazol seizures (Kokka et al, 1993;Kang et al, 1998;Liang et al, 2004). Thus, the profile of decreased ␦ and increased ␣4 and ␥2 subunit expression may predominate in several animal models with increased seizure susceptibility.…”
Section: Responses To Neurosteroids Are Decreased In Pilocarpine-treamentioning
confidence: 65%